2012
DOI: 10.1016/j.bbmt.2011.07.019
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cytotoxic Therapy with Hematopoietic Stem Cell Transplantation in the Treatment of Adult Acute Lymphoblastic Leukemia: Update of the 2006 Evidence-Based Review

Abstract: Clinical research published since the first evidence-based review on the role of hematopoietic stem cell transplantation (SCT) in the treatment of acute lymphoblastic leukemia (ALL) in adults is presented and critically evaluated in this update. Treatment recommendations changed or modified based on new evidence include: (1) myeloablative allogeneic SCT is an appropriate treatment for adult (<35 years) ALL in first complete remission for all disease risk groups; and (2) reduced-intensity conditioning may produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 68 publications
1
43
0
Order By: Relevance
“…5,6 In high-risk patients, the conventional chemotherapy treatment leads to a remission rate of 80-90%, but long-term survival is not superior to 35%. 18 Previous studies had already demonstrated that results after related and unrelated allo-HSCT for adults with ALL were similar. [19][20][21] Allo-SCT from related or matched unrelated donors results in 5-year OS from 40-50% in high-risk patients.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…5,6 In high-risk patients, the conventional chemotherapy treatment leads to a remission rate of 80-90%, but long-term survival is not superior to 35%. 18 Previous studies had already demonstrated that results after related and unrelated allo-HSCT for adults with ALL were similar. [19][20][21] Allo-SCT from related or matched unrelated donors results in 5-year OS from 40-50% in high-risk patients.…”
Section: Discussionmentioning
confidence: 93%
“…Autologous HSCT may be considered in patients lacking a donor, with similar results but higher relapse incidence. 18 In the absence of an HLA-matched donor, CB cells can be used as an alternative source of allo-HSCT. The Spanish group has reported outcomes of 62 high-risk ALL patients receiving UCBT compared with 87 transplanted with matched unrelated donor grafts, with no significant differences in RI, LFS or OS.…”
Section: Discussionmentioning
confidence: 99%
“…Several prospective and retrospective studies have been published on this topic but have produced conflicting data. The guidelines of various major organizations such as the American Society of Blood and Marrow Transplantation, 4 the National Marrow Donor Program (http://marrow.org/ Physicians/When_to_Transplant/Referral_Guidelines.aspx), and the European Blood and Marrow Transplant Group (http://www. ebmt.org/Contents/Resources/Library/EBMTESHhandbook/ Documents/EBMT2008_Cap21.pdf) on the use of allogeneic and autologous HCT in adult patients with ALL in CR1 are not consistent.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 In addition, two retrospective studies showed no difference between related and unrelated HSCT for adult ALL patients, including those in CR1, 12,13 and the recent evidencebased review from the American Society for Blood and Marrow Transplantation supported this. 33,34 However, patients who undergo unrelated HSCT in CR1 are a select population of patients who have maintained their remission status during the donor-coordination process. We performed a decision analysis to identify the optimal strategy for patients with ALL in CR1, who lack an HLA-matched sibling but who have an HLA-matched unrelated donor.…”
Section: Discussionmentioning
confidence: 99%